Synthesis, Characterization, and Electroluminescent Properties of Iridium(III) 2‐Phenylpyridine‐type Complexes Containing Trifluoromethyl Substituents and Various Main‐Group Moieties. Issue 7 (July 2014) - Ho, Cheuk‐Lam; Lam, Ching‐Shan; Sun, Ning; Ma, Dongge; Liu, Li; Yu, Zhen‐Qiang; Xue, Liqin; Lin, Zhenyang; Li, Hua; Lo, Yih Hsing; Wong, Wai‐Yeung
Abstract New heteroleptic cyclometalated iridium(III) 2‐phenylpyridine‐type complexes with trifluoromethyl substituents and various main‐group moieties were synthesized and their photophysical, electrochemical, and electroluminescent (EL) properties studied. The emission color can be tuned by a facile derivatization of the phenyl moiety of 2‐phenylpyridine with various main‐group moieties, and we have prepared new yellowishgreen to orange triplet emitters with enhanced charge injection/charge transporting features, which can furnish attractive EL performance in phosphorescent organic light‐emitting devices (OLEDs). Attempts were also made to fabricate two‐color white‐light OLEDs based on a combination of fluorescent blue and phosphorescent orange emitters.